Analysis of Train Maintenance Capacity with Discrete Event Simulation Modeling: Case Study of Train Depot - Kartikaningtyas, Dela Safitri; Raharno, Sri; Virdyawan, Vani (Jurnal Ilmiah Teknik Industri, 2024)
Indonesian Railways is facing a significant increase in passenger volume year by year, along with the planned arrival of new trains. An expansion of maintenance capacity at the Train Depot is needed due to the current limitations in resources to face the increasing maintenance demands. This research aims to evaluate the current maintenance capacity and provide recommendations for increasing the maintenance capacity with the utilization of discrete event simulation modeling to simulate the train maintenance process based on the current conditions. The simulation considers several scenarios involving adjustments in the number of trains maintained, work shifts, the number of maintenance teams, and maintenance equipment. By enhancing the maintenance capacity at the Train Depot, Indonesian Railways will be able to prevent potential lossess of passenger transport revenue. These recommendations are expected to serve as a basis for decision-making in developing a master plan of train maintenance in the future